2014
DOI: 10.1042/bst20130286
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic shuttling: a common theme in mechanotransduction

Abstract: Cells sense their mechanical and physical environment through diverse mechanisms, and these interactions specify a wide range of responses including growth, survival, migration and differentiation. Although much work has focused on dissecting the adhesive and structural components of the cell responsible for transducing external mechanical forces into biochemical signalling cascades, only recently have studies begun to examine how mechanical signals are transmitted to the nucleus and activate specific gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Consistent for a role of CTGF in IPF, a recent open-label uncontrolled study suggested that a monoclonal antibody targeting CTGF, FG-3019, may be beneficial in a subset of IPF patients in terms of lung function decline and imaging-assessed fibrotic changes [23]. SRF is a transcription factor that is activated by the p38 MAP kinase pathway [24] and by increased extracellular matrix stiffness through mechanotransduction [25]. SRF is essential for collagen-1 expression by lung fibroblasts in vitro [26], while inhibition of the SRF pathway by the small molecule CCG-203971 attenuates lung fibrogenesis in the bleomycin-induced lung fibrosis model in mice [27].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent for a role of CTGF in IPF, a recent open-label uncontrolled study suggested that a monoclonal antibody targeting CTGF, FG-3019, may be beneficial in a subset of IPF patients in terms of lung function decline and imaging-assessed fibrotic changes [23]. SRF is a transcription factor that is activated by the p38 MAP kinase pathway [24] and by increased extracellular matrix stiffness through mechanotransduction [25]. SRF is essential for collagen-1 expression by lung fibroblasts in vitro [26], while inhibition of the SRF pathway by the small molecule CCG-203971 attenuates lung fibrogenesis in the bleomycin-induced lung fibrosis model in mice [27].…”
Section: Discussionmentioning
confidence: 99%
“…To induce changes in the cell's gene expression program, signaling molecules regulated by external forces must be translocated from the cytoplasm into the nucleus and nucleocytoplasmic shuttling has been suggested as a common theme in mechanotransduction (Sharili and Connelly 2014). The SRF (serum-response factor) and YAP (Yes-associated protein)/TAZ (transcriptional coactivator with PDZ-binding motif ) pathways are known mediators of this process in multiple cell types, including keratinocytes.…”
Section: Mechanosensitive Signaling Pathways In the Control Of Desmosmentioning
confidence: 99%
“…A set of non-overlapping responses among the TFrs was also anticipated as RGD is thought to act exclusively through integrins 83 , yet mechanical signals can be relayed by multiple mechanisms, including G-protein coupled receptors, stretch-activated ion channels, actin-coupled TFs, and direct coupling to the nucleus 13, 17, 19, 31, 73 . Furthermore, integrins can coordinate with other receptors and/or signaling components to yield a sensitive and tailored response to the environmental factors, allowing differential responses to biochemical and biophysical features 84 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, tumors are typically much stiffer than healthy tissue and this tissue rigidity may contribute to malignancy 13 . Many aspects of cellular differentiation and disease progression are mediated by interactions of extracellular matrix (ECM) with cytoskeleton-associated, cell membrane receptors that initiate complex cytosolic signaling cascades that lead to activated transcription factors (TFs) in the nucleus 3, 13, 1719 . TFs are powerful regulators of cell phenotype, as evidenced by the development of methods to generate induced pluripotent stem cells by manipulating a few TFs 20 .…”
Section: Introductionmentioning
confidence: 99%